2014
DOI: 10.1186/s13000-014-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P16 in high-risk human papillomavirus related lesions of the uterine cervix in a government hospital, Malaysia

Abstract: BackgroundCervical cancer is one of the most common cancers affecting women worldwide. It is well established that human papilloma virus (HPV) infection is the prime risk factor in the development of cervical cancer. The current screening and diagnostic tests have limitations in identifying the range of lesions caused by HPV. The current study aims to evaluate the diagnostic value of p16 immunohistochemical (IHC) investigation in high-risk human papillomavirus (HR-HPV) related lesions of the uterine cervix in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
(27 reference statements)
1
12
0
1
Order By: Relevance
“…In fact, many reports revealed p16 INK4a overexpression by immunohistochemistry in a very high proportion of neoplasia intraepithelial high grade, 80% to 100% of cervical intraepithelial neoplasia (CIN)2 and almost all CIN3, and in nearly all invasive cervical cancers, with diffuse expression throughout the height of squamous epithelium. 26 29 Thus, these data indicate that p16 INK4a protein expression can be used to improve the histopathological diagnosis of precancerous cervical lesions. 30 …”
Section: Discussionmentioning
confidence: 84%
“…In fact, many reports revealed p16 INK4a overexpression by immunohistochemistry in a very high proportion of neoplasia intraepithelial high grade, 80% to 100% of cervical intraepithelial neoplasia (CIN)2 and almost all CIN3, and in nearly all invasive cervical cancers, with diffuse expression throughout the height of squamous epithelium. 26 29 Thus, these data indicate that p16 INK4a protein expression can be used to improve the histopathological diagnosis of precancerous cervical lesions. 30 …”
Section: Discussionmentioning
confidence: 84%
“…Several studies have reported p16 overexpression in cervical cancer as well as in high grade cervical intraepithelial neoplasia (CIN2-3), [9][10][11] although the clinical importance of these findings remains controversial. A meta-analysis showed that p16 overexpression in cervical cancer specimens appeared to increase overall or disease-free survival rates, indicating a more favorable prognosis.…”
Section: ■Discussionmentioning
confidence: 99%
“…From other experimental and literature data and review articles following should be kept in mind, regarding p16 expression: its level can both increase or decrease depending on tissue.There are great variations in interpretation of what p16 positivity is in some studies. Therefore it is important to find panel of biomarkers necessary for the diagnosis of cervical epithelial especially for the differential diagnosis of the degree of dysplasia in cases borderline from LSIL to HSIL (16,20,21,22).Our result show that p16 expression is one of the most significant biomarkers and diagnostic methods for HPV. This was confirmed both in accordance with the fact that p16 can rarely be positive in the cervical epithelium without dysplasia, but in a different percentage and a different microscopic image of the visualization of it.Thats why we have to be very careful with interpretations of this imunohistochemical marker.…”
Section: Resultsmentioning
confidence: 70%